Sistem Penyiram Otomatis Berbasis IOT Smart Home Pada Tanaman Rumah Menggunakan Arduino Atmega 328P - Nainggolan, Joshua Fines; Poningsih, Poningsih; Irawan, Irawan; Irawan, Eka; Amalya, Nanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A greenhouse is a building with a frame or shaped like bubbles, covered with clear or translucent material that can transmit light optimally for production and protect plants from climatic conditions that are detrimental to plant growth. Research on an Arduino-based plant watering system in a plant house aims to design, create, and test a system to be able to carry out watering. The method used in research on an IOT smartphone-based plant watering system uses an ATMEGA 328P Arduino. There are several stages that need to be paid attention to, namely the design stage, the construction/manufacturing stage, and the installation stage. Next is the testing of products that have been made using Arduino and ESP8266. Watering can be scheduled so that it is done on time. The system can do watering; watering is done automatically with a working voltage of 208–214 VAC and 15 VDC and a constant Arduino pin voltage of 4.8 VDC. By carrying out tests on watering plants, based on the test results, the Arduino-based automatic plant watering system in the plant house can work well according to design.